Impact of diet in shaping gut virome of grain-fed and grass-fed beef cattle revealed by a comparative metagenomic study - Yujie Zhang; Yen-Te Liao; Fang Liu; Robert W. Li; Vivian C. H. Wu (Microbiome)
Abstract Background In the United States beef industry, grain-feeding and grass-feeding are the two most common types of cattle feeding. Different feeding methods are likely to affect gut microbiota compositions and subsequently change microbial adaptation and cattle metabolism. However, there is limited information regarding the impact of diet on cattle gastrointestinal virome. This study examined the composition of fecal virome from grain-fed and grass-fed beef cattle and identified unique virome features to understand the relationship between these two feeding types. Results Six grain-fed and six grass-fed Angus beef cattle were weighed, and their fecal samples were collected for further viral metagenomic sequencing. The difference in animal growth revealed a significantly higher post-weaning weight in grain-fed cattle than in grass-fed cattle after day 56. Furthermore, the analysis of the fecal viral population showed that approximately 795 and 1266 predicted viral sequences were obtained in the grain-fed and grass-fed samples, respectively. Among those, 54.3% of the grain-fed and 26.3% of the grass-fed viral sequences were identified as known viruses. The taxonomic classification showed that viruses belonging to the order Caudovirales, mostly bacteriophages, dominated the cattle virome in both sample groups, followed by the order Cremeviriles and Petitvirales. At the family level, 13 and 16 different viral families were detected in the grain and grass-fed groups, respectively. The comparison of virome features from the two groups indicated that the viral population from the kingdom Bamfordvirae had a significantly higher abundance in the grain-fed group than in the grass-fed cattle virome. In contrast, the kingdom Heunggongvirae had a significantly higher abundance in the grass-fed group than in the grain-fed cattle virome. Moreover, the viruses, belonging to the order Caudovirales and the family Podoviridae, had significantly higher abundances in the grass-fed virome than in the grain-fed virome. Conclusions The findings indicate the influence of animal feeds on the changes in gastrointestinal viral compositions and their potential association with cattle weight gain. The current outcome can contribute to further understanding of phage-bacterial interactions and their underlying mechanisms in regulating the animal host’s metabolism and feed efficiency. Video Abstract